Spexin and Galanin in Metabolic Functions and Social Behaviors With a Focus on Non-Mammalian Vertebrates - Mohd Zahir, Izzati; Ogawa, Satoshi; Dominic, Nisha Angela; Soga, Tomoko; Parhar, Ishwar S. (Frontiers in Endocrinology, 2022)
Spexin (SPX) and galanin (GAL) are two neuropeptides that are phylogenetically related and have descended from a common ancestral gene. Considerable attention has been given to these two multifunctional neuropeptides because they share GAL receptors 1,2, and 3. Since GAL and SPX-synthesizing neurons have been detected in several brain areas, therefore, it can be speculated that SPX and GAL are involved in various neurophysiological functions. Several studies have shown the functions of these two neuropeptides in energy regulation, reproduction, and response to stress. SPX acts as a satiety factor to suppress food intake, while GAL has the opposite effect as an orexigenic factor. There is evidence that SPX acts as an inhibitor of reproductive functions by suppressing gonadotropin release, while GAL modulates the activity of gonadotropin-releasing hormone (GnRH) neurons in the brain and gonadotropic cells in the pituitary. SPX and GAL are responsive to stress. Furthermore, SPX can act as an anxiolytic factor, while GAL exerts anti-depressant and pro-depressive effects depending on the receptor it binds. This review describes evidence supporting the central roles of SPX and GAL neuropeptides in energy balance, reproduction, stress, and social behaviors, with a particular focus on non-mammalian vertebrate systems.